2016
DOI: 10.1186/s12877-016-0182-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of complete blood cell counts with metabolic syndrome in an elderly population

Abstract: BackgroundMetabolic syndrome’s (MetS) role in predicting cardiovascular diseases and diabetes has been confirmed in many large cohort studies. Nontraditionally, hematogram components are significantly related to MetS in many different age groups. However, little is known about its role among the elderly.MethodsWe enrolled 18,907 subjects over the age of 65 years who underwent regular health examinations. They were divided into three groups according to age: young old (YO: ≥ 65 and < 74 years old), old old (OO:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 37 publications
2
6
2
1
Order By: Relevance
“…In the present study, subjects with higher FPG levels had the second highest hazard ratio among the other MetS components. This finding contradicts the results of our previous reports and several other major studies in populations of other ages . In these studies, compared to other MetS components, FPG has always been shown to be less related to other parameters such as uric acid, haemoglobin, or insulin resistance.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the present study, subjects with higher FPG levels had the second highest hazard ratio among the other MetS components. This finding contradicts the results of our previous reports and several other major studies in populations of other ages . In these studies, compared to other MetS components, FPG has always been shown to be less related to other parameters such as uric acid, haemoglobin, or insulin resistance.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding contradicts the results of our previous reports and several other major studies in populations of other ages. [22][23][24] In these studies, compared to other MetS components, FPG has always been shown to be less related to other parameters such as uric acid, haemoglobin, or insulin resistance. This contradiction can be explained by the complex interaction between insulin secretion and resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally normocytic anemia is common among hypertensive patients. Lower hemoglobin concentrations were found in patients with uncontrolled than among those with well controlled HTN, indicating a higher cardiovascular risk in uncontrolled HTN . In this study, HGB and HCT mean values did not differ significantly between hypertensive hyperuricemic subjects and nonhypertensive hyperuricemic subjects.…”
Section: Discussioncontrasting
confidence: 52%
“…More concretely, it has been evidenced that the number of circulating neutrophils, monocytes, and lymphocytes are positively correlated with BMI, body fat, and insulin resistance [38]. Moreover, the prevalence of MetS and MetS components increases white blood cell count in both men and women, which may be useful as a marker of low-grade systemic inflammation and cardiovascular disease risk [39,40].…”
Section: Discussionmentioning
confidence: 99%